KAJIAN HUKUM PENCEGAHAN ANTI PENCUCIAN UANG DAN PENDANAAN TERORISME PADA LEMBAGA KEUANGAN - Hanuring Ayu; Dika Yudanto (Universitas Janabadra, 2019)
The perpetrators of terrorism will never succeed in carrying out their actions without various forms of other supporting facilities and instruments, one of which is funding support. In terrorism activities funds are urgently needed to promote ideology, finance theorists and their families, fund travel and lodging, recruit and train new members, falsify identities and documents, buy weapons and to design and implement operations. Funding for terrorism can come from illegal activities such as kidnapping, robbery, piracy, drugs, bartering / trading, or the results of legal businesses owned by terrorists, donations to foundations or NGOs, or cash couries. In order to prevent and eradicate the entry or availability of funds intended to carry out terrorism activities, the Government of Indonesia together with the House of Representatives has succeeded in establishing Law Number 9 of 2013 concerning Prevention and Eradication of Criminal Acts on financing terrorism. Forms of terrorism financing prevention: Applying the principle of recognizing users of financial services; Reporting and monitoring compliance with PJK (Financial Services providers); Supervision of money transfer activities through the transfer system or sending money through other systems; Supervision of the carrying of cash and or other payment instruments into or outside the Indonesian customs area; blocking the flow of terrorism funds. Funding for terrorism is cross country so that prevention and eradication efforts are carried out by involving financial service providers, law enforcement officials, and international cooperation to detect the existence of a flow of funds used or allegedly used to fund terrorism activities.